(untitled) (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To share our experience of capacity building in the electronic and print media sector of Bangladesh for fistula related awareness. Methods: We identified key media institutions and professional press forums in Bangladesh. We provided fourhours orientation training to 96 professionals from electronic and print media and other media related institutions in six workshops. We also provided an information pack for fistula communication. From the workshops we identified focal persons within the organizations for fistula and maternal health communication. Results: Over 120 reports, editorials, features, news were published in papers and 67 television and radio program were broadcasted after the workshops. A range of topics were covered in the press including early marriage prevention, fistula related event coverage and promoting care-seeking behaviors for fistula suffers. Conclusion: The Media Leaders workshop was very well accepted by the professional press and other media personnel. The training led to an increased capacity in mass communication on fistula. It is anticipated that the increased awareness of media personnel will result in continued contributions in the future.